Potentialities of Bacillus strains for promoting growth in maize (Zea mays L.) - Rojas, Marcia M.; Tejera, B.; Bosh, Diana M.; Rios, Y.; Rodríguez, Janet; Heydrich, Mayra (Cuban Journal of Agricultural Science, 2016)
The Bacillus genus has representatives promoting plant growth. The objective of this research was to isolate and select bacteria from Bacillus genus, associated to the maize cultivation with potential in promoting growth in this crop of great importance in human and animal feeding. Isolations of bacteria belonging to this genus were carried out, endophytes as rhizosphere, of maize (Zea mays L.) hybrid cultivar P-7928. The isolates were physiologically characterized, in terms of indolic compounds production, the phosphate solubilization capacity and qualitative determination of biological nitrogen fixation. Also, the ability to form biofilms was evaluated using the method crystal violet stain on polystyrene plates. Later, the isolates with better results were entirely selected through a cluster analysis. A total of 19 isolates, 9 rhizosphere and 10 endophytes were obtained. All produce indole-acetic acid in a concentration range between 2.92 and 17.02 μgmL-1 and fix atmospheric nitrogen; nine solubilize inorganic phosphate in a range between 12.16 and 33.07 μgmL-1. Furthermore, the ability to form biofilms of 78.94% of the isolates was showed, which gives advantages in the colonization of plants. The formation of in vitro biofilm of a good strain producing and a nonproducing was compared. Both were adhered to the polystyrene plate with different pattern, which was more consistent in the EAM4 strain, with high biofilm production. The obtained results allowed selecting the native isolates ERM1, RM5, EAM5 and RM1 as the most promising to promote plant growth and their future use in the sustainable agriculture. Key words: Bacillus, plant growth promoting bacteria, phosphates solubilization